Pulling the chariot of the sun : a memoir of a kidnapping - McCrae, Shane, 1975- (Scribner, 2023)
"An unforgettable memoir by an award-winning poet about being kidnapped from his Black father and raised by his white supremacist grandparents. When Shane McCrae was three years old, his grandparents kidnapped him and took him to suburban Texas. His mom was white and his dad was Black, and to hide his Blackness from him, his maternal grandparents stole him from his father. In the years that followed, they manipulated and controlled him, refusing to acknowledge his heritage--all the while believing they were doing what was best for him. For their own safety and to ensure the kidnapping remained a success, Shane's grandparents had to make sure that he never knew the full story, so he was raised to participate in his own disappearance. But despite elaborate fabrications and unreliable memories, Shane begins to reconstruct his own story and to forge his own identity. Gradually, the truth unveils itself, and with the truth, comes a path to reuniting with his father and finding his own place in the world."--